2004
DOI: 10.1158/0008-5472.can-03-1952
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf 3 Inhibits Invasion and Motility of Saos-2 Osteosarcoma Cells by Modulating the Wnt-β-Catenin Pathway

Abstract: Osteosarcoma (OS) is a primary malignancy of bone with a tendency to metastasize early. Despite intensive chemotherapy and surgical resection, ϳ30% of patients still develop distant metastasis. Our previous work using clinical OS samples suggested that expression of the Wnt receptor LRP5 might be associated with tumor metastasis. In the present study, we used a Dickkopf (Dkk) family member and a dominant-negative LRP5 receptor construct to modulate Wnt signaling in OS cells. Saos-2 cells, which ectopically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
236
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(259 citation statements)
references
References 37 publications
19
236
3
1
Order By: Relevance
“…It has been reported that an invasion index, corrected for cell motility, indicates specific contribution of ECM degradation and is of use to evaluate invasiveness of tumor cells (Albini, 1998;Hoang et al, 2004). In fact, significantly decreased invasion index was obtained when SaOS-2 cells were transfected with Ror2 siRNA #1 compared with control siRNA #1 transfection (Figure 2e).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been reported that an invasion index, corrected for cell motility, indicates specific contribution of ECM degradation and is of use to evaluate invasiveness of tumor cells (Albini, 1998;Hoang et al, 2004). In fact, significantly decreased invasion index was obtained when SaOS-2 cells were transfected with Ror2 siRNA #1 compared with control siRNA #1 transfection (Figure 2e).…”
Section: Resultsmentioning
confidence: 84%
“…The cells were incubated for 8 h (migration assay) or 24 h (invasion assay) (U2OS cells were incubated for 12 h (invasion assay)) and then the membranes were fixed in 3.7% formaldehyde. The evaluation of migrating or invasive cells was carried out as previously described (Hoang et al, 2004;Nishita et al, 2006). An invasion index was calculated as follows: (number of invasive cells per number of migrating cells) Â 100 (Albini, 1998;Hoang et al, 2004).…”
Section: Reporter Assaymentioning
confidence: 99%
“…As a Wnt antagonists, it is reported that DKK3 overexpression does not affect nuclear/cytoplasmic accumulation of β‐catenin 11. On the other hand, another article has shown that overexpression of DKK3 leads to a reduction in the cytoplasmic level of β‐catenin in SaOS‐2 cells 31. In a previous report, Xiang et al .…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the expression of Wnt antagonists are often down‐regulated in several human cancers and DKK3 was no exception 29. There are reports on DKK3 both enhancing and repressing the Wnt signalling pathway 30, 31. Recently, DKK3 was also reported as playing distinct roles in different human pancreatic cancer cells, but not much is known about the detailed mechanism 20, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, DKK3 is also known as 'REIC' (Reduced Expression in Immortalized Cells) . Furthermore, DKK3 overexpression suppresses tumor cell growth (Hoang et al, 2004;Abarzua et al, 2005;Lodygin et al, 2005;Kawano et al, 2006). While hypermethylation of human DKK3 correlates with …”
Section: Dkks and Cancermentioning
confidence: 99%